Current interventional model for movement in Parkinson’s disease: network meta-analysis based on the improvement of motor ability - HongFei, Zhao; Li, Zhang; Liang, Li; Ru, Guo Wan; Yi, Huang Lan; Zhen, Wang (Frontiers in Aging Neuroscience, 2024)
Aim: To identify optimally therapeutic exercise interventions for improving motor ability among patients with Parkinson's disease (PD), we conducted a network meta-analysis (NMA) of randomized controlled trials comparing different exercise regimens. Methods: Relevant RCTs were retrieved by searching PubMed, Embase, Cochrane, Web of Science, CINAHL, CBM, China National Knowledge Infrastructure (CNKI), Wan fang, VIP, and other databases from inception to July 9, 2023 is available in English as the primary language. Exercise outcomes as measured by Movement Disorder Society-Unified Parkinson's Disease Rating Scale Part III (MDS-UPDRS-III) score change were evaluated and ranked using STATA software version 18.0. All included studies were assessed for methodological quality using the Cochrane Risk of Bias tool. Results: The final NMA included 71 studies involving 3,732 participants, 87 intervention experiments, and 27distinct interventions. Although most exercise interventions showed some efficacy (reducing MDS-UPDRS-III score), cumulative ranking probability surface (SUCRA) values indicated that the best exercise interventions for motor function improvement were archery (95.6%), riding a bicycle (80.9%), and binary rhythm dance (80.8%). Conclusion: An exercise intervention comprising archery, cycling, and(or) binary rhythm dance may yield superior improvements in motor function among patients with Parkinson's disease. Network meta-analysis (NMA) is a versatile technique for simultaneously comparing multiple interventions (e.g., A vs. B, B vs. C) from individual studies (Lu & Ades, 2004). Moreover, by combining direct and indirect comparisons, NMA techniques can rank the relative efficacies of multiple interventions for selecting the optimal regimen (Garcia-Ruiz et al., 2014). In the current NMA, the MDS-UPDRS was selected as the outcome measure and various exercise interventions evaluated in randomized controlled trials (RCTs) were systematically ranked according to the improvement (decrease) in MDS-UPDRS score post-intervention. The first part of the MDS-UPDRS addresses "non-motor experiences of daily living", the second "motor experiences of daily living", the third part remains dedicated to "motor examination", and the fourth part focuses on "motor complications". The third part, MDS-UPDRS-III (motor examination) has demonstrated high reliability, validity, and sensitivity to change following treatment, with an assessment time of less than 15 minutes (Goetz et al., 2008).